Biology - Campbell, Neil A. (Pearson Education, 2005)
Neil Campbell and Jane Reece's BIOLOGY remains unsurpassed as the most successful majors biology textbook in the world. This text has invited more than 4 million students into the study of this dynamic and essential discipline.